Pengentasan Kemiskinan Berbasis Pemberdayaan Masyarakat Di Kabupaten Pohuwato - Rusni Djafar; Umar Sune (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2019)
This study aims to explain and analyze empowerment-based poverty alleviation programs through the activities of assistance, facilitation and promotion and determinant factors of success in empowerment-based poverty eradication in Pohuwato District. This research method using qualitative approach, descriptive type to get a complete picture of problem of resource development of apparatus. The results of the research show that the assistance activities through training, consultation and technical assistance, and similar activities have not been coordinated with other supporting programs, making it difficult for the facilitator task as a program facilitator. Empowering the poor through the provision of facilities, has not been able to improve the capacity of the community. The low capacity and quality of service of government apparatus from the local level to the rural level, so that the provision of facilities does not allow the involvement of the poor. A highly centralized bureaucratic system and a highly authoritarian political system that has been practiced for more than four decades in Indonesia, brings out the weaknesses of the bureaucratic character. Promotion activities in the context of empowering the poor as an activity aimed at developing responsive services, the reality has not been effective in helping facilitate the poor to access various development programs that are beneficial to improving the welfare of the poor by earning productive employment. Activities that require synergies of cooperation between institutions / organizations (Government, Private, NGOs), difficult to realize because the dominance of egoism interests of each stakeholders in addressing every village development program. It is recommended to optimize training, consultation and technical assistance activities, as well as similar activities coordinated with support programs. Provision of adequate supporting facilities that can empower the poor on an ongoing basis, and streamline promotion to develop responsive services that enable poor people to access programs.Need to pay attention to communication factor, resources, attitude, and bureaucracy structure,so asnot tohinder the smooth implementation of poverty eradication program based on empowerment society.